SUKSESI BISNIS KELUARGA: SINKRONISASI NILAI TRADISI JAWA DAN PRINSIP KEADILAN ISLAM DALAM KELANGSUNGAN USAHA KECIL: Family Business Succession: Synchronizing Javanese Traditional Values and Islamic Principles of Justice in the Sustainability of Small Enterprises - Agapito Barros (Business, Accounting and Management Journal, 2025)
The continuity of family businesses faces crucial challenges during intergenerational succession, where failure rates often increase sharply from the first to the second and subsequent generations. This study aims to explore the mechanisms of value transfer in family business succession in the Micro, Small, and Medium Enterprises (MSMEs) sector, particularly in the batik industry center of Central Java. The main focus of the study is how business actors synchronize Javanese traditional values ​​(local wisdom) with the Islamic principle of justice (Al-'Adl) to ensure business sustainability. This research uses a qualitative method with a phenomenological case study approach. Data collection was conducted through in-depth interviews, participant observation, and documentation in five batik business families that have survived for more than two generations. The results show that successful succession depends not only on the transfer of capital assets but also on the transmission of "moral capital." A unique value synchronization model was identified: (1) The concept of Mikul Dhuwur Mendhem Jero (upholding the honor of parents) is reinterpreted through the lens of Birrul Walidain to maintain business reputation; (2) The principle of mutual cooperation is transformed into Islamic brotherhood in employee management and supply chain relations; and (3) The division of authority and business inheritance balances Faraid law with the principle of meritocracy-based professional management. This study contributes to the business ethics literature by proposing that integrating ethno-religious values creates "social immunity," strengthening MSME resilience in the face of market volatility.